The world population and its expected future evolution - Marie Prášilová; Pavla Hošková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2010)
Population numbers on Planet Earth grow steadily. The most rapid increase took place over the 20th century when the number of world population rose from 1.6 billion up to 6 billion. Demographic revolution affect the process of changes. The paper has paid attention to the relationship between natality and mortality in various parts of the world. It indicates the differing behaviour in the African countries where the demographic revolution has not been finished so far. Population numbers on the Planet Earth are being forecast for 2050 applying the exponential smoothing methods. The outcomes of statistical procedures are being compared with the UN prognoses and they do not indicate large differences in confidence intervals predictions. The adaptive procedures selected have been found suitable and satisfying for the population numbers forecasting purposes. Most rapidly the population of Africa numbers will grow until 2050, the number of Europeans will cover 7.55 % of the world population only.